Nano-Se crosstalks with nano-DOX/FU to selectively hack hepatic cancer cells and spare normal cells healthy: A mechanism-based study - Aziza B. Shalby, Ahmed A. Abd-Rabou, Hanaa H. Ahmed (Journal of Applied Pharmaceutical Science, 2017)
Egypt became as one of the hot spots in the international map of hepatocellular carcinoma (HCC). HCC is the second cancer type in Egyptian men and the sixth in Egyptian women. Selenium (Se) is one of the known essential elements for human beings, its deficiency is linked with aliments, while its dosage over the recommended daily allowance appears to protect against some cancer types. The purpose of the present study was to hack hepatic cancer cells and spare normal cells healthy using the crosstalk mechanism of nano-Se with nano-DOX or nano-FU. We used liver cancer HepG2 versus normal kidney BHK-21 cell lines as models to investigate the antiproliferative action of Se, FU (5-fluorouracil), and DOX (doxorubicin) nanoformulations. We recorded that individual treatments with nano-Se, nano-FU, or nano-DOX promote both HepG2 and BHK-21 cell death in a dose dependent manner. On the contrary, nano-FU or nano-DOX when combined with nano-Se selectively triggers HepG2 cell death, while sparing BHK-21 cells proliferating in a healthy state. Moreover, Se nanoformulation potentiates nitric oxide (NO) and malondialdehyde (MDA) re-homeostasis when combined with DOX and FU nanoformulations to avoid harming BHK-21 normal cells; this is associated with slight bioenergetic deprivation through glycolytic inhibition. Interestingly, we also observed that individual and combinatorial Se nanoformulation crosstalks with Zinc to kill cancer cells. Conclusively, targeting of redox mode and glucose consumption using Se, FU, DOX nanoformulations may provide a new vision for tackling hepatocellular carcinoma specifically, not normal cells.
Keywords: Nano-Se, nano-FU, nano-DOX, HepG2 cell line, tumor inhibition.